Trąd w porządku teologicznym „Zwiastowania” Paula Claudela - Kucab, Mateusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article analyses the issue of leprosy as a sign of accepting God’s will, which comes from the order of faith and is far from rational. Being infected with the disease by the main character symbolizes the boundless trust of Providence and the recognition of her life calling. Although affliction is a source of exclusion and fear from the community, for the girl it is an expression of love and an honor to participate in the Creator’s plan. Leprosy, causing great medieval epidemics, is not only important for the dramaturgy, but also for the ideological significance of the work, which is helped by the references to the philosophical writings of Paul Claudel.
Leprosy in the Theological Order of Paul Claudel’s „The Annuciation of Mary”
Keywords: Bible; absurdity; illness; gift; mystery; faith; Biblia; absurd; choroba; dar; tajemnica; wiara